The Study of Teaching Reading Comprehension During Online Class in Diponegoro Senior High School Student’s Perception - Vincencia Carolina Salim (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Â Abstract: The purpose of this study was to investigate students' perceptions of teaching online reading comprehension, which included class management and activity during online class, student obstacles, students' perceptions of teaching reading during online class, students' perceptions in reading, and classroom management. This study used descriptive qualitative research. The subjects were four students from each class of social science major of SMAS Diponegoro Tumpang. Then to collect the data, the researcher takes teacher document and conducted in-depth-interviews as the research instrument. The researcher conducted in-depth interviews to collect the data. The researcher conducted in-depth interviews to collect the data. The researcher found three main points of students' perception. First, the teacher managed the class using a platform of Google Classroom, Google Meet, Zoom, and Whatsapp. For the reading class activity, students analyze and interpret the text from any sources. Second, it was about the student's faced the obstacles such as unstable signals and a lack of explanation by the teacher. Finally, all participants state that during learning reading online, they enjoyed the class and give them new experienced in online learning. Student understand the explanation of the material given by the teacher, and the teacher will review the material at the end of the lesson. Students in the class participate in both of discussion group and question and answer session, from this online class, they feel that their reading ability quite improved than before. Based on the findings, this study had a limited scope and several limitations. It will be better in the future to add another instrument and a different method. The suggestion was addressed to the teacher to increase students' enthusiasm in an online reading lesson, and the teacher should add interactive and interesting exercises.Keywords: Reading Comprehension, Online Learning, Studentsâ€™ Perception